Development and Testing of a Hybrid Measure of Muscle Strength in Juvenile Dermatomyositis for Use in Routine Care. Issue 9 (12th August 2018) - Varnier, Giulia Camilla; Rosina, Silvia; Ferrari, Cristina; Pistorio, Angela; Consolaro, Alessandro; Bovis, Francesca; Dalprà, Sara; Pilkington, Clarissa; Maillard, Susan; Civino, Adele; Tsitsami, Elena; de Inocencio, Jaime; et al.
Abstract : Objective: To develop and test a hybrid measure of muscle strength for juvenile dermatomyositis (JDM), which is based on the combination of the Manual Muscle Testing in 8 muscles (MMT‐8) and the Childhood Myositis Assessment Scale (CMAS) but is more comprehensive than the former and more feasible than the latter. Methods: The hybrid MMT‐8/CMAS (hMC) is composed of all 8 items of the MMT‐8 and 3 items of the CMAS: time of head lift, assessment of abdominal muscles, and floor rise. The score ranges 0–100, with 100 indicating normal muscle strength. Validation procedures were conducted using 3 large multinational patient samples, including a total of 810 JDM patients. Results: The hMC revealed face and content validity, good construct validity, excellent test–retest reliability (intraclass correlation coefficient = 0.99), and internal consistency (Cronbach's α = 0.94), strong responsiveness to clinical change over time (standardized response mean = 0.8 among patients judged as improved by the caring physician), and satisfactory capacity to discriminate patients judged as being in the states of inactive disease or low, moderate, or high disease activity by the physician ( P < 0.001) or patients whose parents were satisfied or not satisfied with the illness course ( P < 0.001). Conclusion: The hMC was found to possess good measurement properties in a large population of patients with a wide range of disease activity and severity. The new tool, which is primarily intended for use in routine clinical care, should be further tested in other populations of patients evaluated prospectively.